Outcome of preterm babies with respiratory distress syndrome on nasal CPAP - B., Sunil; N., Girish; Bhuyan, Manali (International Journal of Contemporary Pediatrics, 2017)
Background: Continuous positive airway pressure (CPAP) has become a useful modality in management of respiratory distress in preterm babies. Nasal CPAP was found to be safe and effective means of treating mild and moderate RDS and apnoea of prematurity; Continuous Positive Airway Pressure (CPAP) is a cost-effective and minimal invasive respiratory support for the newborn. The aim of the study was to assess whether the introduction of continuous positive airway pressure (CPAP) results in improved respiratory outcomes in preterm neonates ≤36 weeks of gestation in KIMS hospital. Methods: The study was an observational clinical study, undertaken in KIMS hospital, Bangalore, Karnataka, between November 2015 to October 2016. All babies born ≤36 weeks of gestational age with respiratory distress were included in this study. Chi-square/ Fisher Exact test has been used to find the significance of study parameters on categorical scale between two or more groups and Non-parametric setting for Qualitative data analysis Results: Seventy-seven premature newborn babies with ≤36 weeks of gestation were included in the study and were put on nasal CPAP. The incidence of CPAP failure was 22.1% (95% CI 14.27-32.54%). The proportion of neonates who required surfactant was 16.9% (10.14-26.77%) and the proportion of children who met with mortality was 6.5% (10.14-26.77%) in this study. Conclusions: Early institution of CPAP in the management of RDS in premature neonates can significantly reduce the need for mechanical ventilation (MV) and surfactant therapy.